Sistem Informasi Administrasi Sekolah Dasar (Studi Kasus : SD Negeri 2 Lingkis) - Greta Guardi Falla; Rusmala Santi; Evi Fadilah (APTIKOM SUMSEL, 2020)
Primary schools are educational institutions which are the main source educational data needed by education actors to carry out their duties and profession. All activities of recording or recording data in the school are called with administration, administration in schools there are many kinds and types, one of them student administration. Student administration, there are various kinds of activities carried out, starting from enrollment of new students until students leave the school. And management student administration currently running at SD Negeri 2 Lingkis is currently not very good management, especially in storage so that we need an information system Can support the activities of recording data and reports on school student administration. Purpose This research is to build an Elementary School Student Administration Information System which will be more effective and efficient to support all data recording and reporting activities which will be built with a web-based information system. The method used in the development of the school administration information system is Prototype where this prototype model consists of communication, planning, modeling, construction and delivery . The result of this research SD Negeri 2 Lingkis can make it easier for registranst, student, teacher, administrators and principals in student administration